2010
DOI: 10.1111/j.1740-0929.2010.00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and hormonal regulation of adiponectin and its receptors in bovine mammary gland and mammary epithelial cells

Abstract: Although the functions of adiponectin, a differentiated adipocyte-derived hormone, in regulating glucose and fatty acid metabolism are regulated by two subtypes of adiponectin receptors (AdipoRs; AdipoR1 and AdipoR2), those in ruminants remain unclear. Therefore we examined the messenger RNA (mRNA) expression levels of adiponectin and its receptors in various bovine tissues and mammary glands among different lactation stages, and the effects of lactogenic hormones (insulin, dexamethasone and prolactin) and gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…Here, we establish that FGF21 is among the endocrine factors that confer the important properties of breast milk and contribute to the maturation of the neonatal gastro-intestinal system, at least in the current rodent model. Maternal blood, rather than the mammary gland, appears to be the main source of milk FGF21; this is similar to previous findings for EGF 20 and IGF-II 21 , but contrasts with those for leptin and adiponectin 13 22 . Consistent with a previous report 23 , we observed high blood FGF21 levels in lactating dams.…”
Section: Discussionsupporting
confidence: 86%
“…Here, we establish that FGF21 is among the endocrine factors that confer the important properties of breast milk and contribute to the maturation of the neonatal gastro-intestinal system, at least in the current rodent model. Maternal blood, rather than the mammary gland, appears to be the main source of milk FGF21; this is similar to previous findings for EGF 20 and IGF-II 21 , but contrasts with those for leptin and adiponectin 13 22 . Consistent with a previous report 23 , we observed high blood FGF21 levels in lactating dams.…”
Section: Discussionsupporting
confidence: 86%
“…This result suggests these lactogenic hormones regulate CMKLR1 expression to modulate the regulatory effect of chemerin on genes associated with lactogenesis in mammary epithelial cells during the lactation cycle. Our previous studies showed that adiponectin expression in mammary glands decreases in the peak and late-lactation period, although adiponectin receptor 1 (AdipoR1) expression increases in the same period [28]. Serum adiponectin concentrations are higher 2e3 weeks after parturition in Holstein cows [29]; another study showed decreased plasma adiponectin protein levels at parturition with a recovery within 2 months [30].…”
Section: Discussionmentioning
confidence: 97%
“…2003). Our previous report showed that adiponectin mRNA levels in mammary glands were significantly lower at lactational stages than at non‐lactational stages (Ohtani et al . 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although these results may be specific in ruminants, these mechanisms are still unclear. Our previous report showed that AdipoR1 mRNA levels increased at peak lactation in bovine mammary tissues and GH and lactogenic hormones (insulin, prolactin and dexamethasone) regulated the levels of AdipoR2 mRNA expression in bovine mammary epithelial cells (Ohtani et al . 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation